The ACE2/Angiotensin-(1–7)/Mas Receptor Axis: Pleiotropic Roles in Cancer - Xu, Juanjuan; Fan, Jinshuo; Wu, Feng; Huang, Qi; Guo, Mengfei; Lv, Zhilei; Han, Jieli; Duan, Limin; Hu, Guorong; Chen, Lian; Liao, Tingting; Ma, Wanli; et al. (Frontiers in Physiology, 2017)
Cancer remains one of the most common causes of death and disability and represents a major economic burden in industrialized nations. The renin-angiotensin system (RAS) has been well recognized as one of the most important regulators of both normal and pathological physiological processes in the brain, kidney, heart and blood vessels. The activation of the angiotensin-converting enzyme 2/angiotensin-(1-7)/mitochondrial assembly receptor (ACE2/Ang-(1-7)/MasR) axis, which is one component of the RAS, has recently been identified as a critical component of pulmonary systems, gastric mucosa and cancer. However, the ability of the ACE2/Ang-(1-7)/MasR axis to suppress or promote cancer has not been fully elucidated. In this review, we focus on recent experimental and clinical studies investigating the basic properties, roles and mechanisms of ACE2, Ang-(1-7), and the MasR, as well as the axis pathway, to provide insights into possible therapeutic strategies for treating cancer that target the ACE2/Ang-(1-7)/MasR axis.